UPAYA MENINGKATAN MOTIVASI DAN HASIL BELAJAR MELALUI METODE ROLE PLAYING BERORIENTASI KEARIFAN LOKAL PADA MATERI JUAL BELI DI KELAS 4 SDN BULUS - Gita Kumalasari; Titi Anjarini, Suyoto (STKIP Subang, 2025)
This study aims to improve student motivation and learning outcomes through a Role Playing method oriented to local wisdom on the topic of buying and selling in Grade 4 at SDN Bulus. The research used Classroom Action Research (CAR) with Kurt Lewin's model, involving planning, action, observation, and reflection. Data were collected through observation sheets, questionnaires, tests, and documentation. The results showed significant improvements in student motivation and learning outcomes after implementing the Role Playing method. Student motivation increased from 56.62% in the pre-cycle to 81.94% in cycle II, while average learning outcomes improved from 44.28 to 82.85. This indicates that the Role Playing method oriented to local wisdom effectively enhances motivation and learning achievement in elementary school students.